Hardeman Lodge - McNeal, W. W. (Book collections on Project MUSE., 2020)
"It is the mid 1870s, and the railroad being built westward toward San Antonio will eventually connect Texas to California. Luling, one of the towns springing up along the route, is the end of the line for a year or so. Established in 1874 a few miles east of the San Marcos River, Luling is a melting pot of humanity. Later known as the toughest town in Texas, it is a haven for gamblers, outlaws, and 'ladies of the night.' Hardeman Lodge follows some of the characters introduced in Plum Creek (TCU Press, 2016) as they meet the challenges that life presents them. Billy McCulloch faces some tough moral choices as he embarks upon the practice of law. Ada Adams and Everett Hardeman become engulfed in a crisis arising from her marriage to a cruel husband. And the indomitable Lily Poe is forced to deal with tragedy. In spite of lingering racial prejudice and streaks of lawlessness, principles of justice and fair play still live in the hearts of most of the characters who come near Hardeman Lodge."--Publisher press release.